Food Peculiarities of Small Ukrainian Gentry in the XIX - early XX century - Васянович, Олександр (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article deals with the peculiarities of daily food and festive meals of the small Ukrainian gentry, which are considered on archival, field and printed materials. Attention is focused on the desire of the gentry to show their own ambition, to distinguish themselves from the surrounding peasantry in the way of eating. It was found out that food of the gentry and the peasantry, being in similar social and economic conditions, had many common features, but gradually the influence of urban culture on the gentry’s meal spread.